An integrated photonic chip of measurement-device independent quantum key distribution (MDI-QKD) - Cao, Lin (2021)
An integrated chip of MDI-QKD system is demonstrated. The system generates a key rate per pulse of 2.923 × 10^-6 over a distance corresponding to 50-km optical fibre with 25% detection efficiency.